The existence-uniqueness theorem for a system of differential equations in the spaces l2r+1 - Allahabi, Fateh Abdo Ali (Universiti Putra Malaysia Press, 2011)
We study an infinite system of differential equations of the second order. Some special cases of the system result from application of the decomposition method to some hyperbolic equations. We discuss the existence and uniqueness questions in the space l2r+1. The proved theorem enables us to investigate some optimal control and differential game problems described by such a system.